PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI SEBAGAI STRATEGI PEMASARAN PRODUK UMKM DIMASA PENDEMI COVID-19 DI DESA SEMBAWA KECAMATAN JALAKSANA KABUPATEN KUNINGAN - Rio Andriyat; Sugeng Supriyadi; Nunu Nugraha; Indah Suci Rahmawati; Diaz Athya Rahma (Politeknik Negeri Sriwijaya, 2022)
Abstract Indonesia has declared COVID-19 as a non-natural disaster in the form of a disease outbreak that must be taken care of so that there is no increase in cases. Covid-19 caused a health crisis and disrupted national economic activities, one of which was in the UMKM sector (Micro, Small and Medium Enterprises) in Kuningan district. Based on BPS data from Kuningan Regency, there are 192 UMKM in Jalaksana District, out of 5151 UMKMs fostered by DINAS. The Micro, Small and Medium Enterprises (UMKM) sector is one of the sectors most affected by the Covid-19 pandemic. Covid-19 has disrupted supply and demand as well as supply chains. Many UMKMs in Kuningan Regency were forced to stop their production. One of the national economic recovery efforts carried out by the government during the Covid-19 pandemic is to encourage the UMKM sector to take advantage of the role of ICT (Information and Communication Technology). The use of ICT in the era of the Covid-19 pandemic, is highly prioritized, especially as a strategic step in marketing UMKM products. Large-scale social restrictions in the era of the covid-19 pandemic require people to adapt to new habits. adaptation of new habits in carrying out all routines, one of which is by utilizing ICT in various fields, such as communicating and transacting. This is an important point in the UMKM product marketing strategy during the COVID-19 pandemic by implementing ICT. Keywords: ICT, COVID-19, UMKM Products.